The Relationship between Job Satisfaction and Organizational Commitment to Employee Turnover Rate at PT Trans Rekreasindo during the Covid 19 Pandemic - Subranta, Aris; Iswadi, Udi; Dzikri, Ahlu (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This study aims to determine whether job satisfaction and organizational commitment have a direct effect on Employee Turnover. Quantitative research uses a correlational approach. The population of this study is 90 employees at PT Trans Rekreasindo. The sample consisted of 90 employees. Saturated sampling was used in this study. Research instruments made by researchers guided by dimensions and expert indicators are used to collect data through survey methods. The Likert scale with five alternative answer options ranging from strongly agree, agree, doubt - doubt, disagree, and strongly disagree was used in the questionnaire. Data analysis was carried out using SPSS Version 20 The findings of this research said 1) the result of the job satisfaction variable tcount of 6.123 was greater than the ttable so the tcount > ttable so that the influence of the job satisfaction variable significantly on employee turnover 2) the organizational commitment variable tcalculated of 1.709 showed that the tcount > ttable, significance 0.091 < 0.05 so the organizational commitment variable had no significant influence on employee turnover 3) the results of the simultaneous test showed a value of F = 21.644 and a significance value < probability of 0.000 < 0.05 so the variables Job satisfaction and organizational commitment had a positive and significant influence on employee turnover.